System Control ChatBot - Lokeshwari, N; Harsha Vardhan, G; V, G; Manasa, A.V.V; N. Mounica, (International Journal of Computer Sciences and Engineering, 2020)
Chatbot is another new way for people to interact with a computer system. Traditionally, to get a reply by a software program involved using a search engine. Humans simply ask questions to the chatbot to get answered by the chatbot in a most efficient way. This Paper Builds a general purpose that makes conversations between user and computer. Initially the Chatbot has Given all instructions Related to your Computer. If User doesn't Know How to Work with a computer he can ask any related thing about it. The Bot we are trying to build is related to computers i.e. Windows OS version 10 and Above.